Evaluating the effect of mobile applications “My A:Care” and “Smart Coach” on adherence to lipid-lowering treatment in patients with dyslipidemia: a prospective, randomized, open-label clinical study - Pongchaiyakul, Chatlert; Driessen, Stefan (Frontiers in Digital Health, 2025)
BackgroundDyslipidemia, a key modifiable risk factor for cardiovascular diseases, is managed using lipid-lowering therapies. Medication adherence for dyslipidemia treatment is poor across the globe, impacting treatment effectiveness. This highlights the need for scalable strategies, such as mobile app-based behavioral interventions, to enhance adherence to lipid-lowering therapies.ObjectiveThe study assesses the impact of “My A:Care” and “My A:Care Smart Coach” mobile interventions on adherence to dyslipidemia treatment.MethodsThis proof-of-concept, open-label, single-center study randomized 150 patients with suboptimal adherence to dyslipidemia treatment into three groups (1:1:1): My A:Care, My A:Care Smart Coach (intervention), and a no-app control group. Participants were monitored over 12 weeks. The primary objective was to assess changes in medication adherence, with secondary outcomes including changes in lipid parameters and beliefs about lipid-lowering medications. The study also explored the association between adherence and app engagement.ResultsAt week 12, the Medication Adherence Report with Visual Analog Scale (MARS-5VA) Part 1 scores were modestly, but significantly lower in the control group compared to the intervention groups: Mean (SD); No-App: −0.3 (0.9), Smart Coach: 0.0 (0.7) [p = 0.035], My A:Care-All: 0.0 (0.7) [p = 0.056]. Compared to the control, the intervention groups also showed greater improvements in non-HDL-C levels [% change (SE): My A:Care-All: −5.5% (3.2), Smart Coach: −4.3% (3.7), No-App: −1.8% (3.7)], along with favorable trends in TC, LDL-C, and HDL-C.ConclusionThis proof-of-concept study suggests that the My A:Care and Smart Coach apps may positively impact adherence to lipid-lowering therapy in patients with dyslipidemia. The positive adherence outcomes and potential benefits in lipid control indicate promising early signals that warrant further investigation in larger, confirmatory studies. Clinical Trial RegistrationNCT05370703.